Corncob waste as a potential filler in biocomposites: A decision towards sustainability - Sandeep Gairola; Tejas Pramod Naik; Shishir Sinha; Inderdeep Singh (Composites Part C: Open Access, 2022)
Waste resource utilization is of utmost importance today in order to promote circular economy and sustainable development. The current research work focuses on utilizing post-consumer corncob (CC) waste into value-added products by exploring its potential as a filler/additive in polypropylene (PP) composites. If successful, the added fillers will substitute 5-20% PP without compromising the functional requirements of non-structural (non-load bearing) products. Corncob filler (CCF) at four-filler loadings (5, 10, 15, and 20 wt.%) and two variants of particle size (S1-100-355 µm and S2-355-710 µm) was melt-compounded using an extruder and then injection molded into composite samples. The effect of filler size and loading was investigated on water diffusion kinetics, mechanical, thermal, and flammability characteristics for analyzing the performance of developed materials during in-service conditions. Thermal and flammability characteristics were analyzed by thermo-gravimetric analysis (TGA), Ul-94 horizontal burning (HB), and limiting oxygen index (LOI) test. CCF-S1 exhibited better mechanical properties with higher tensile and flexural modulus than CCF-S2. For 10 wt. % loading, lower size (S1 filler) showed 5.85% and 2.94% increase in tensile and flexural modulus, respectively than higher filler size S2. CCF-S1 filled composites record lowered HB rate than S2 filler with no notable change in LOI values. The results revealed the possible reuse and utilization of CCF as a reinforcing filler at 10% loading with a filler size of 100-355 µm. The properties achieved using CCF and extrusion injection molding process are significant enough for non-structural applications such as paper weight, tableware, mementos etc.